2005
DOI: 10.1002/art.20765
|View full text |Cite
|
Sign up to set email alerts
|

Increased CD4+ T cell infiltrates in rheumatoid arthritis–associated interstitial pneumonitis compared with idiopathic interstitial pneumonitis

Abstract: Objective. To study lymphocyte markers in rheumatoid arthritis (RA)-associated interstitial pneumonitis (IP) compared with idiopathic IP.Methods. Paraffin-embedded lung biopsy specimens from patients with RA (n ‫؍‬ 15) and from those without RA (n ‫؍‬ 16), all of whom had a diagnosis of either nonspecific IP or usual IP, were studied. Tissue sections from each patient were reviewed by a pathologist, who was blinded to the clinical data. Age and pulmonary function test results were similar in RA and non-RA pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 43 publications
6
59
0
2
Order By: Relevance
“…Our data show that they populate rheumatoid lesions outside the joint, such as in the lung (Figures 5A and B). We previously reported that the lungs of patients with RA-associated IP are characterized by infiltration of CD4ϩ T cells (28). Our present data further show that such lung-infiltrating cells are also CD56ϩ.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Our data show that they populate rheumatoid lesions outside the joint, such as in the lung (Figures 5A and B). We previously reported that the lungs of patients with RA-associated IP are characterized by infiltration of CD4ϩ T cells (28). Our present data further show that such lung-infiltrating cells are also CD56ϩ.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the frequency of these cells was also higher in patients with RA-associated IP than in those with idiopathic IP only. We had previously examined these same tissue blocks and reported that CD16ϩ,CD4Ϫ,CD3Ϫ NK cells were rarely found in the lung tissues (28). The present data indicate that the serially positioned CD4ϩ,CD56ϩ,CD3ϩ cells in the lung lesions are T cells.…”
Section: Cd56؉ T Cells Are Oligoclonal Lymphocytes Oligoclonal Cd28-supporting
confidence: 59%
See 3 more Smart Citations